Prevention of acute GI disturbances with a functional food formulation designed to support and maintain intestinal barrier function during sports performance - Sponsiello, Nicola; Belgeri, Stefano; Conte, Roberto; Carandini, Daniele; Salamone, Maurizio (Progress in Nutrition, 2015)
Gastrointestinal disturbances are very frequent among athletes undergoing strenuous and continuous training and an endurance race. We tested a mix of nutrients and antioxidants for preventing GI disturbances and dropouts at the “Tor des Geantes” ultratrail competition (330 km run). Athlets used the mix during training and competition and showed benefits, including more power and resistance and better gastrointestinal health. Even if not all of athletes took the mix on a regular basis during the race, the number of athletes pulling out of the race due to gastrointestinal problems was 4.2% (1/24) in the treatment group compared to 11.3% (6/52) in the control group.